Tactile priming modulates the activation of the fronto-parietal circuit during tactile angle match and non-match processing: an fMRI study - Yang, Jiajia; Yu, Yinghua; Kunita, Akinori; Huang, Qiang; Wu, Jinglong; Sawamoto, Nobukatsu; Fukuyama, Hidenao (Frontiers in Human Neuroscience, 2014)
Repetition of a stimulus task reduces the neural activity within certain cortical regions responsible for working memory (WM) processing. Although previous evidence showed that the repetition of vibrotactile stimuli reduced the activation in the ventrolateral prefrontal cortex, whether the repeated tactile spatial stimuli triggered the priming effect correlated with the same cortical region remains unclear. Therefore, we used event-related functional magnetic resonance imaging and a delayed match-to-sample task to investigate the contributions of the priming effect to tactile spatial WM processing. Fourteen healthy volunteers were asked to encode three tactile angle stimuli during the encoding phase and one tactile angle stimulus during the recognition phase, and then, they answered whether the last angle stimulus was presented during the encoding phase. As expected, both the Match and Non-Match tasks activated a similar cerebral network. The critical new finding was decreased brain activity in the left inferior frontal gyrus (IFG), right posterior parietal cortex (PPC) and bilateral medial frontal gyrus (mFG) for the match task compared to the Non-Match task. Therefore, we suggest that the tactile priming engaged repetition suppression mechanisms during tactile angle matching, and this process decreased the activation of the fronto-parietal circuit, including IFG, mFG and PPC.